Fume extractor for anode mud smelting - LUO MINGRU; MA YUTIAN; AN GUORUI; WU JIANMING; GUO SHAOMIN; JIA XIAODONG; DAI JIANJUN; WANG XING (2013)
The utility model discloses a fume extractor for anode mud smelting, and relates to a fume extractor applied to a smelting process for extracting valuable metal from anode mud generated in the electrolytic process. The fume extractor structurally comprises a driving motor, a coupler, a shaft sealing box, a fan shell, a fan air inlet, fan impellers, a fan air outlet, a motor base, a fan base, a fan sealing body and a rotating shaft. The fume extractor is characterized in that three fan impellers are provided and are sequentially fixed on the rotating shaft inside the fan shell. According to the fume extractor for anode mud smelting, the fan of an air exhaust device is improved, the requirements on properties of high negative pressure and lower flow are met, and meanwhile high corrosion resistance of equipment is ensured. Requirements on air exhaust and valuable metal recycling in the anode mud pyrogenic attack process are met, the recycling rate of metal is improved, the air leakage of the equipment is reduced